A Contest without Winners : How Students Experience Competitive School Choice - Phillippo, Kate (Book collections on Project MUSE., 2019)
"With a focus on Chicago Public High Schools, A Contest without Winners argues that competitive choice policy intensifies and exacerbates socioeconomic inequalities. Phillippo examines how urban infrastructure, income inequality, and racial segregation all shape policy enactment and interpretation as policymakers and educators ask students to compete for access to public resources. Her study amplifies the voices of students regarding how policies shape their lives, revealing how the individuals most impacted by school choice policy experience it academically, developmentally and civically"--